In-store surveillance technologies: what drives their acceptability among consumers?. Issue 5 (20th October 2022) - Brooksbank, Roger; Scott, Jonathan M.; Fullerton, Sam
ABSTRACT: Retail surveillance technologies that enable marketers to track the in-store behaviour of an individual consumer are becoming commonplace. Yet, despite questions raised about their ethicality, their acceptability from a consumer perspective remains under-researched, thereby limiting a marketer's ability to make informed decisions when deploying such technologies. Accordingly, this study focuses on a 'matched pair' of widely used technologies selected specifically for the purpose of examining its core proposition that a voluntary, transparent form of surveillance that provides the consumer with direct benefits (Shopkick), will be viewed more favourably than will its equal and opposite counterpart (Shopperception). Building on the theoretical perspective of the Technology Acceptance Model (TAM), a sample of 477 survey respondents provided reasons why each technology might, or might not, be acceptable using an essentially open-ended questionnaire. Responses were coded and labelled with the subsequent lists of reasons being analysed descriptively. A single closed-ended question required respondents to rate their overall acceptability, and these responses were subject to t-tests. A comparison of the results obtained across two independent subsamples show that consumers evaluate 'Shopkick' to be considerably more acceptable than 'Shopperception', thereby confirming the study's core proposition whilst also providing insights into the specific 'costs and benefits' associated with each technology from the consumers' point of view. The study's findings and their implications are then delineated from the perspective of both practitioners and academicians. For practitioners, an easy-to-use 'infographic' visual decision-making aid designed to help retailers make more informed choices about if and how to best to deploy the new generation of in-store surveillance technologies is developed. For academicians with a focus on theoretical considerations, a variation of the TAM as it relates to the consumers' propensity to accept or reject an in-store surveillance technology is also proposed.